GaInSn liquid nanospheres as a saturable absorber for an Er:CaF2 laser at 2.75 μm - Chen, Bo; Li, Kuan; Jin, Yicheng; Wang, Peifu; Zhang, Ning; Zhang, Ke; Liu, Shande; Xu, Jinlong (Frontiers in Physics, 2022)
High-quality GaInSn liquid nanospheres are successfully fabricated by the ultrasonic method as a novel saturable absorber in the mid-infrared range. An open-aperture Z-scan technique is applied to study the saturation absorption property, presenting a modulation depth of 34.3% and a saturable fluence of 0.497 GW/cm2 at 2.3 μm, respectively. With GaInSn nanospheres as a saturable absorber, a stable Q-switched Er:CaF2 crystal laser operating at 2.75 μm is realized. The maximum Q-switched output power of 361 mW is obtained under the absorbed pump power of 2.9 W. The shortest pulse width of 500 ns and the highest repetition rate of 67 kHz are generated, corresponding to maximum peak power and single pulse energy of 10.78 W and 5.39 μJ, respectively. These findings indicate a promising potential of GaInSn nanospheres SA for generating nanosecond mid-infrared laser pulses.